Local economic transformation, digitalization, and poverty reduction: The moderating role of Islamic financial inclusion in Luwu Regency - Ernawati, Ernawati; Abdullah, Muh. Ruslan; Ishak, Ishak (Journal of Islamic Economics Lariba, 2026)
IntroductionPoverty remains a persistent development challenge in Indonesia, particularly in regional economies where economic growth does not always translate into inclusive welfare improvement. In Luwu Regency, poverty continues to reflect limited income, weak productive capacity, unequal access to economic opportunities, and insufficient integration between local development, digital technology, and financial services. Local economic transformation and digitalization are increasingly viewed as strategic pathways for strengthening productivity, expanding market access, empowering micro, small, and medium enterprises, and improving household welfare. At the same time, Islamic financial inclusion offers a Sharia-compliant mechanism for broadening access to financing, savings, digital financial services, and financial literacy.ObjectivesThis study analyzes the effects of local economic transformation and digitalization on poverty in Luwu Regency, South Sulawesi, Indonesia. It also examines whether Islamic financial inclusion strengthens the relationship between local economic transformation, digitalization, and poverty reduction.MethodThis study used a quantitative approach with a cross-sectional research design. Data were collected through structured questionnaires from 250 respondents consisting of micro, small, and medium enterprise actors and users of digital services in Luwu Regency. The data were analyzed using Structural Equation Modeling based on Partial Least Squares to assess the measurement model, structural model, direct effects, and moderating effects.ResultsThe findings show that local economic transformation, digitalization, and Islamic financial inclusion have significant direct effects on poverty reduction. Local economic transformation contributes through regional productivity improvement, local resource utilization, and enterprise empowerment. Digitalization supports poverty reduction by expanding access to digital transactions, online markets, and economic information. Islamic financial inclusion also contributes by improving access to Sharia-compliant financial services. However, Islamic financial inclusion does not significantly moderate the relationship between local economic transformation and poverty, while it significantly strengthens the relationship between digitalization and poverty reduction.ImplicationsThe findings suggest that poverty alleviation requires integrated policies that combine local economic empowerment, digital infrastructure, digital literacy, and broader access to Islamic financial services.Originality/NoveltyThis study contributes to regional development and Islamic economics literature by integrating local economic transformation, digitalization, and Islamic financial inclusion into a single framework for explaining poverty reduction at the regional level.